Naval power - Black, Jeremy (Palgrave Macmillan, 2009)
Jeremy Black provides a short and accessible account of naval power and its relationship to international relations. Focusing on navies as instruments of power and analyzing what they indicate about the nature of state systems and cultures, he provides an overview of key debates within this increasingly popular field.